TRANSFORMASI DIGITAL PELAYANAN PUBLIK DALAM MENINGKATKAN KEPUASAN MASYARAKAT DI INSTANSI PEMERINTAH - Aunulla, Dia Puspita Indah; Edhib Harits Anugrah (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the effectiveness of digital transformation in improving public satisfaction through technological integration in government institutions, while identifying inhibiting factors such as infrastructure limitations and digital literacy to formulate an inclusive and sustainable service model. This research employs a qualitative approach with a literature review method, synthesizing various findings from national and international academic databases published between 2019 and 2025. The results indicate that digital integration significantly enhances service efficiency, transparency, and public accountability, as evidenced by innovations like the SIMPEDA application which reduced processing times from days to minutes. However, the study identifies several critical barriers, including unequal internet infrastructure in remote areas, low digital literacy among certain demographics, and public skepticism regarding data security. The novelty of this research lies in the proposal of a hybrid service model that bridges the digital divide through innovative leadership, human resource competency development, and cross-sector collaboration. The implications of these findings suggest that for digital transformation to be sustainable, government agencies must prioritize data protection and user-friendly interfaces. This research provides a strategic framework for policymakers to ensure that the transition to e-government promotes social inclusion and delivers professional, high-quality public services.